Magneto-Optical Probe for Investigation of Multiphase Fe Oxide Nanosystems - Campo, Giulio; Pineider, Francesco; Bonanni, Valentina; Albino, Martin; Caneschi, Andrea; de Julián Fernández, César; Innocenti, Claudia; Sangregorio, Claudio (Chemistry of materials, 2015)
In iron oxide nanoparticles the transformation of the metastable magnetite phase to maghemite, through the oxidation of iron, often represents a major drawback for correct interpretation of their physical properties and their effective use in several applicative areas. To solve this issue we propose an innovative method for identifying the chemical composition of complex ferrite nanostructures based on magneto-optical (MO) spectroscopy. Spherical iron oxide nanoparticles with increasing size are investigated by magnetic circular dichroism (MCD) in the nUV–vis–nIR range (350–1000 nm). Particular attention is dedicated to the time evolution of the MO response, which is ascribable to the oxidation process of the nanomaterial. The measured MCD spectra show a complex line shape due to the overlap of several MO transitions. Deconvolution analysis of MCD hysteresis loops allows the interpretation of this complex response as the combination of two distinct contributions, originating from magnetite and maghemite domains in the nanoparticles. We consider this method a viable complement to conventional techniques for the discrimination of the two magnetic phases in nanostructured materials.